Comparative Effects of Using Whatsapp and Google Classroom on Language Testing Subject - Lollo Rosa Lubis (ITScience (Information Technology and Science), 2021)
Since the coronavirus disease (Covid-19) was present in Indonesia, the government took a policy to conduct the online teaching-learning process. Some applications were used in conducting the teaching-learning process. Two applications are most used in South Tapanuli namely WhatsApp and Google Classroom because these applications had the widest range. Based on the background, the research was conducted to investigate whether there were any significant effects of using WhatsApp and Google Classroom on Language Testing subjects in the fifth-semester students of the Education Institute of South Tapanuli. Quasi-experimental was applied (pretest and posttest design) with 25 students for WhatsApp class (experimental class 1) and 25 students for Google Classroom (experimental class 2). Furthermore, the independent sample t-test as the parametric statistics couldn't be used to determine the hypothesis because the data was not normal distribution so the Mann Whitney U test was used which is equivalent to the independent sample t-test. The result of the pretest showed that both groups didn’t give any significant difference because the Man Whitney U test showed Asymp.Sig (2-tailed) was more than 0.05 (0.600>0.05). The result of the posttest showed that both groups didn’t give significant differences either because the Man Whitney U test showed Asymp.Sig (2-tailed) was more than 0.05 (0.541>0.05). This calculation showed there were no significant effects of using WhatsApp and Google Classroom on Language Testing subjects among the fifth-semester students of the Education Institute of South Tapanuli. In other words, this calculation gave us that the use of WhatsApp and Google Classroom gave almost the same effect.